Analysis of fetal fraction in non-invasive prenatal testing with low-depth whole genome sequencing - Xiaolei Xie; Weiguo Yin; Fuguang Li; Suxia Xuan; Yu Ouyang (Heliyon)
Background: The fetal fraction (FF) is a critical factor influencing the performance of non-invasive prenatal testing (NIPT). Different NIPT methods and sequencing depths can lead to distinct minimum FF thresholds for Trisomy 21 (T21). This study aims to analyze the minimum FF thresholds for detecting T21 in PCR-free NIPT using a low-depth whole genome sequencing method. Methods: A total of 71 non-pregnant women and 4827 pregnant women were enrolled for a study investigating the impact of FF on NIPT testing. Results: The results showed a weak negative correlation between cfDNA levels and age in non-pregnant women. There was no statistically significant difference in the ratio of chromosome 13, 18, and 21 between pregnant and non-pregnant women. The minimum FF required for 100 % detection of trisomy 21 was determined to be 5 % in PCR-free NIPT using a low-depth whole genome sequencing method. Analysis of a large sample revealed that 4.43 % of pregnant women exhibited FF below 5 %, with those having lower FF showing significantly higher maternal weight compared to those near the median. Furthermore, FF demonstrated a significant negative correlation with the weight of pregnant women; specifically, an FF of 5 % at 12–19 weeks corresponded to a weight of 96 kg, while at 20–22 weeks it corresponded to a weight of 93 kg. Conclusions: These results suggest that the FF below 5 %, or pregnant women weighing over 93 kg, should be given more attention in clinical genetic counseling.